Determinants of Optimal Breastfeeding Practices in Indonesia: Findings From the 2017 Indonesia Demographic Health Survey - Siti Nurokhmah; Setyaningrum Rahmawaty; Dyah Intan Puspitasari (Korean Society for Preventive Medicine, 2022)
Objectives Understanding the factors influencing mothers' decision to breastfeed their infants is essential to formulate effective breastfeeding interventions. This study explored the determinants of optimal breastfeeding indicators in Indonesia. Methods We used the 2017 Indonesia Demographic and Health Survey to analyze factors associated with early initiation of breastfeeding, exclusive breastfeeding (EBF), and continued breastfeeding at 1 year (CBF-1) and 2 years (CBF-2). Multivariate logistic regression models were used to examine bio-demographic, socio-cultural, and behavioral characteristics associated with breastfeeding after considering the survey design effect. Results The risk of delayed breastfeeding initiation was higher among infants who were born smaller, first-born children, were delivered via cesarean delivery, and did not have immediate skin-to-skin contact (p<0.01). Infant's age, birth pattern, household wealth index, and the mother's occupation and smoking status were predictors of EBF (p<0.05). CBF-1 was less common among first-time mothers and those working in the non-agricultural sector, mothers from wealthier families, and mothers who had cesarean deliveries (p<0.01). Infant's age was negatively associated with CBF-2 (adjusted odds ratio [aOR], 0.85; 95% confidence interval [CI], 0.74 to 0.99). Mothers attending college were less likely to practice CBF-2 than those with no education or primary education (aOR, 0.45; 95% CI, 0.26 to 0.77). The absence of postnatal visits was a risk factor for CBF-1 and CBF-2 (p<0.05). Conclusions Breastfeeding interventions in Indonesia should pay particular attention to at-risk groups such as women from wealthier families, working outside the agricultural sector, and with a higher education level. Nutrition-sensitive programs (e.g., postnatal care and smoking cessation) should also be encouraged.